Analisis Pembatasan Usia (Ageism) Pencari Kerja dalam Prespektif Hak Asasi Manusia (HAM) - Pangestu, Gema Ramadhanu Ridho Ing (UM Purwokerto Press, 2024)
The practice of ageism in the workplace is being discussed phenomenon. Age restrictions applied by the agency/company as the qualification of job seekers is assessed as discriminatory, unfair, detrimental, and not in line with the concept of human rights. This investigation aims to analyze the practice of age restrictions in human rights prospects. The research is carried out using a sociological jurisprudential method that emphasizes the facts found in the field. The results of the research show that the practice of age restrictions for job seekers assessed has limited the opportunities of the public to get a decent job and has been judged as an unobjective phenomenon. On the other hand, some countries in the world have abolished the practice of age restrictions, such as Germany, the Netherlands, and the United States.